A recurrent mitochondrial p.Trp22Arg NDUFB3 variant causes a distinctive facial appearance, short stature and a mild biochemical and clinical phenotype. Issue 9 (18th April 2016) - Alston, Charlotte L; Howard, Caoimhe; Oláhová, Monika; Hardy, Steven A; He, Langping; Murray, Philip G; O'Sullivan, Siobhan; Doherty, Gary; Shield, Julian P H; Hargreaves, Iain P; Monavari, Ardeshir A; Knerr, Ina; et al.
Abstract : Background: Isolated Complex I deficiency is the most common paediatric mitochondrial disease presentation, associated with poor prognosis and high mortality. Complex I comprises 44 structural subunits with at least 10 ancillary proteins; mutations in 29 of these have so far been associated with mitochondrial disease but there are limited genotype-phenotype correlations to guide clinicians to the correct genetic diagnosis. Methods: Patients were analysed by whole-exome sequencing, targeted capture or candidate gene sequencing. Clinical phenotyping of affected individuals was performed. Results: We identified a cohort of 10 patients from 8 families (7 families are of unrelated Irish ancestry) all of whom have short stature (<9th centile) and similar facial features including a prominent forehead, smooth philtrum and deep-set eyes associated with a recurrent homozygous c.64T>C, p.Trp22Arg NDUFB3 variant. Two sibs presented with primary short stature without obvious metabolic dysfunction. Analysis of skeletal muscle from three patients confirmed a defect in Complex I assembly. Conclusions: Our report highlights that the long-term prognosis related to the p.Trp22Arg NDUFB3 mutation can be good, even for some patients presenting in acute metabolic crisis with evidence of an isolated Complex I deficiency in muscle. Recognition of the distinctive facial features—particularly when associated with markers of mitochondrial dysfunction and/or Irish ancestry—should suggest screening for the p.Trp22Arg NDUFB3 mutation to establish a genetic diagnosis, circumventing the requirement of muscle biopsy to direct genetic investigations.